Capacitisme et (néo)racisme au sein des processus de classement scolaires au Québec : interprétations par les intervenants des difficultés des élèves issus de l’immigration - Tya Collins; Corina Borri-Anadon (Recherches en Éducation)
The school placement processes of students from immigrant backgrounds considered in “difficulty” is an international concern at the intersection of works relating to special education and those concerning the school experiences of students from immigrant backgrounds or racialized groups. The research problem of this article concerns the identification of these students as disabled or as having adjustment or learning difficulties. From a perspective anchored in Disability Critical Race Studies, this ethnographic study documents different interpretations of perceived difficulties made by school actors with regards to seven primary school students from immigrant backgrounds. Five interpretation-types are presented : 1) medicalization by dismissal of cultural markers, 2) medicalization by professional constraint, 3) medicalization by cultural deficit, 4) precautionary wait, and 5) cultural differentialism. Our results help to shed light on the special education overrepresentation phenomenon regarding these students and to understand how ableism and (neo)racism contribute to it.